2012
DOI: 10.1111/clr.12054
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic and cytokine gene expression of implant‐adherent cells in humans

Abstract: Implants with superimposed nanoscale topography generate a greater induction of genes linked to osteogenesis and cell-cell signaling during the early phases of osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 41 publications
(75 reference statements)
3
35
0
2
Order By: Relevance
“…This is in agreement with results in experimental studies, in normal uncompromized rat model, which revealed higher early expression of bone formation and remodeling factors in cells adherent to surface‐modified implants compared to machined implants . A human study showed that implants with combined nanosurface and microsurface modification enhanced the early expression of osteogenic factors OC and osterix, in implant‐adherent cells, compared to cells adherent to micro‐rough implants . Taken together, the present and previous data suggests that different surface modifications trigger the early osteogenic differentiation in the implant‐adherent cells in bone‐implant interface zone, and, importantly, this is at least partly mirrored in the crevicular fluid around the implant.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with results in experimental studies, in normal uncompromized rat model, which revealed higher early expression of bone formation and remodeling factors in cells adherent to surface‐modified implants compared to machined implants . A human study showed that implants with combined nanosurface and microsurface modification enhanced the early expression of osteogenic factors OC and osterix, in implant‐adherent cells, compared to cells adherent to micro‐rough implants . Taken together, the present and previous data suggests that different surface modifications trigger the early osteogenic differentiation in the implant‐adherent cells in bone‐implant interface zone, and, importantly, this is at least partly mirrored in the crevicular fluid around the implant.…”
Section: Discussionsupporting
confidence: 92%
“…(Bryington et al. ) demonstrated the influence of the presence of nanofeatures (OS) in mediating an immunomodulatory effect on macrophages by enhanced expression of IL‐9 (a Th2‐associated cytokine that reduces monocyte oxidative burst and TNF‐ α release; Pilette et al. ) and IL‐22 compared with microroughened surfaces (TiO).…”
Section: Discussionmentioning
confidence: 99%
“…(Bryington et al. ) were able to demonstrate a differential upregulation of OSX, a key transcription factor for osteoblast differentiation on the nanoscale featured implants compared with the microtopography TiOblast surface. A possible factor contributing to this difference is the age of the population included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, machined implants exhibited higher marginal bone loss and were more prone to failure than oxidized implants after five years (Sayardoust et al., ). Studies in humans which addressed the genes expressed at different implant surfaces during early osseointegration (Bryington, Mendonca, Nares, & Cooper, ; Donos et al., ; Ivanovski et al., ; Thalji, Nares, & Cooper, ) revealed different patterns of expression depending on the surface of the implant (Shanbhag, Shanbhag, & Stavropoulos, ). Common to these studies was the use of a method involving miniature implants, subsequently explanted from the recipient jaw with or without the retrieval of the surrounding bone.…”
Section: Introductionmentioning
confidence: 99%